(untitled) (Scientific journal of the Fergana State University, 2025)
The composition of the essential oil of dry horseradish leaves grown in the Fergana region was studied using gas chromatography-mass spectrometry. According to the results of the study, 21 compounds were found in the essential oil of horseradish leaves, of which 15 compounds were identified, which makes up 94.58% of the total number of detected compounds. The essential oil contains nitriles, heterocyclic compounds, unsaturated hydrocarbons, aldehydes, and terpenoids. The main compounds of the essential oil are 3-butenenitrile (48.3%); 10-methyl-9-nonadecene (13.40%); (2R, 4S)-2,4-dimethyl-5-hexen-1-ol (9.95%); phenylacetaldehyde (4.6%); 1-(5(methyl-2-furanyl)-1-buten-3-one (3.6%); 1H-pyrrole (2.2%) and (-)-isocaryophyllene (2.1%) were found.